Childbirth and occupational mobility : evidence from a longitudinal study - Brannen, Julia [Verfasser] (My University, 1989)
"In Britain most women's employment careers are interrupted by childbirth; only a tiny proportion return to their pre-birth jobs and a considerable proportion experience downward mobility when they do return to work. Evidence is presented from a longitudinal study of two groups of women in the first three years of motherhood: those who resumed their former jobs after maternity leave and those who resigned from the labour force. The paper traces the divergencies occuring in women's employment histories over three years and examines their implications for occupational mobility, taking account of finer shades of mobility than occupational status. Attention is also paid to the ways in which women define and manage occupational mobility in the construction of their employment careers." (author's abstract) ((en)) Die Studie untersucht den Berufsverlauf von Müttern in Grossbritannien. Insbesondere wird der beruflichen Mobilität von Frauen bei der Rückkehr ins Erwerbsleben nachgegangen. (IAB)
Geburt und berufliche Mobilität. Ergebnisse einer Längsschnittuntersuchung
Keywords: G 1.3.3 Bildungs- & Erwerbsbiografien; G 2.3.2 Arbeits- & Beschäftigungsverhältnisse; P 1.1 Jugendliche; G 1.3.3.3 Mobilität; G 2.3.1 Arbeitsteilung & -organisation; G 1.3.3.4 Wiedereingliederung; G 1.2.2.3 Beschäftigungsformen; Frauen; Berufsverlauf; Kind; Auswirkung; Berufliche Mobilität; Mütter; Berufliche Reintegration; Vollzeitarbeit; Teilzeitarbeit